PENGUATAN SPRITUAL JAMA’AH MUSLIM MODERAT MELALUI AKTIVITAS SARWOAN DI DUSUN MENCEK DESA SERUT KECAMATAN PANTI KABUPATEN JEMBER - Hafid; M. Khotibul Umam (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2022)
In religious social life the occurrence of differences is a natural phenomenon experienced by community groups. Attitudes that transgress to the point of breaking the fabric of harmony are caused by differences in affiliations which if left unchecked will become a big problem for the integrity of a nation. This article raises the phenomenon of differences in the body of Islam in the Sarwoan congregation of the Ranubedali village community which consists of fathers. Through activities that can strengthen the character of a mutawasith or moderate Muslim ideally a father who acts as the head of the household can foster a moderate Muslim character to his family and closest environment. This research uses a field study with descriptive qualitative analysis.. The results of this study indicate that understanding the character of moderate Muslims in the Sarwoan congregation is implemented through regular lectures by the leaders of the congregation which contains moderate Islamic values and is supported by routine religious activities carried out together in anjangsana to produce indicators as Muslims who remain harmonious in different backgrounds. to the strengthening of the sovereignty of the Unitary State of the Republic of Indonesia.